Slip band formation at free surface of lath martensite in low carbon steel. (15th February 2019) - Inoue, Junya; Sadeghi, Alireza; Koseki, Toshihiko
Abstract: Cross-sectional observations of the deformation bands formed during in situ tensile observation at the free surface of both ultralow- and low-carbon lath martensitic steels were conducted. The cross-sectional observations clearly revealed the formation of steps along substructure boundaries of the ultralow-carbon lath martensite during deformation. In contrast, severe undulation indicating strain accumulation was observed in the vicinity of high-angle boundaries for the low-carbon lath martensite, and no clear steps were formed along substructure boundaries, even though small filmlike ferrites were found. The "greasy-film" mechanism proposed by Maresca [Maresca et al., Modelling and Simulation in Materials Science and Engineering 24(2016)025006, Maresca and Curtin, Acta Materialia 134(2017)302] as well as the plastic instability theory proposed by Dao and Asaro [Dao and Asaro: Mech. Mater., 23(1996)71] was examined considering the non-Schmid effects and the anisotropic activation of slip systems in lath martensite. Graphical abstract: Image 1